2017
DOI: 10.1093/mnras/stx1141
|View full text |Cite
|
Sign up to set email alerts
|

Overdensities of SMGs around WISE-selected, ultraluminous, high-redshift AGNs

Abstract: We investigate extremely luminous dusty galaxies in the environments around WISEselected hot dust obscured galaxies (Hot DOGs) and WISE /radio-selected active galactic nuclei (AGNs) at average redshifts of z = 2.7 and z = 1.7, respectively. Previous observations have detected overdensities of companion submillimetre-selected sources around 10 Hot DOGs and 30 WISE /radio AGNs, with overdensities of ∼ 2 − 3 and ∼ 5 − 6, respectively. We find that the space densities in both samples to be overdense compared to no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 94 publications
(163 reference statements)
6
28
0
Order By: Relevance
“…Luminous radio-loud AGN at 1.2 < z < 3 have been found to systematically reside in galaxy overdensities on arcminute scales (e.g., Ivison et al 2000;Smail et al 2003;Wylezalek et al 2013;Rigby et al 2014;Malavasi et al 2015;Jones et al 2015;Silva et al 2015). Similar studies for radio-quiet AGN have also revealed galaxy overdensities around them (e.g., Utsumi et al 2010;Capak et al 2011;Morselli et al 2014;Jones et al 2017), although contradictory results have been reported (Kikuta et al 2017;Mazzucchelli et al 2017). Furthermore, halo masses of luminous AGN have been estimated through clustering studies, which either found that they reside in overdensities (e.g., Croom et al 2002;Coil et al 2009) or in normal environments (Coil et al 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Luminous radio-loud AGN at 1.2 < z < 3 have been found to systematically reside in galaxy overdensities on arcminute scales (e.g., Ivison et al 2000;Smail et al 2003;Wylezalek et al 2013;Rigby et al 2014;Malavasi et al 2015;Jones et al 2015;Silva et al 2015). Similar studies for radio-quiet AGN have also revealed galaxy overdensities around them (e.g., Utsumi et al 2010;Capak et al 2011;Morselli et al 2014;Jones et al 2017), although contradictory results have been reported (Kikuta et al 2017;Mazzucchelli et al 2017). Furthermore, halo masses of luminous AGN have been estimated through clustering studies, which either found that they reside in overdensities (e.g., Croom et al 2002;Coil et al 2009) or in normal environments (Coil et al 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Both sets of companion sources have similar WISE colors, Jones et al (2017). When comparing with the WISE color-color diagram of different galaxy populations in Figure 12 in Wright et al (2010) and Figure 26 in Jarrett et al (2011), the companion sources lie in both the starburst (star-forming) galaxy zone and AGN zone.…”
Section: Properties Of Companion Sourcesmentioning
confidence: 83%
“…This could be due to differences in redshift and/or radio emission. However, more observations are needed because only 10 targets in each sample have known redshifts, Jones et al (2017).…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations